People Management in the Establishment of Leadership by Gontor (Success Team Class Six at Pondok Modern Darussalam Gontor for Girls First Campus) - Anwar, Saepul; Jihadi, Lillahi Akbar; Syarifah; Rama Gesta, Mutiara Erisqi; Ahmadan, Madani (Jurnal Penelitian Pendidikan, 2025)
This study aims to examine the concept and implementation of people management in shaping leadership spirit at Pondok Modern Darussalam Gontor For Girls Campus 1 through a case study of the Class 6 Success Team. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results of the study show that the concept of people management at Gontor refers to the process of guidance and education to shape the character and identity of students through planning, organizing, implementing, and supervising. The Success Team acts as a dynamizer that manages the activities of final year students with a character education approach based on the values of Panca Jiwa Gontor, such as sincerity, simplicity, independence, ukhuwah Islamiyah, and freedom. Supporting factors for the success of this team include the number of assignments, the active role of mentors, and the habit of discipline, while inhibiting factors include a lack of initiative, communication, and concern. The implementation of people management has proven to be effective in shaping the leadership spirit of female students who are not only organized but also have strong and resilient leadership characteristics.